Air Pollution and Respiratory Diseases During The Hajj Season in The Holy City of Makkah - Mukhtar Ikhsan (Indonesian Society of Respirology (ISR), 2022)
The holy city of Makkah is one of the big cities in Saudi Arabia that is densely populated, especially during the Hajj season. In recent years, air pollution in Makkah has been a growing problem due to construction activities, motor vehicle fumes, rising temperatures, rainfall and humidity. The higher the level of air pollution exposure, the more it has an impact on human health, especially the lungs and airways. The health impacts associated with air pollution include an increase in the incidence of respiratory infections, asthma, chronic obstructive pulmonary disease and other lung diseases. Better knowledge of the correlation between air pollution and lung and airway diseases will contribute to developing more strategies to reduce air pollution in the holy city of Makkah.